PENERAPAN MEDIA PEMBELAJARAN SMART CITIZEN SPINNER (SCS) PADA JAM PELAJARAN TERAKHIR MATERI SEJARAH PANCASILA UNTUK MENINGKATKAN MINAT BELAJAR PESERTA DIDIK KELAS VII H DI SMP NEGERI 12 SURABAYA - Yunia Risnawati; Nanik Setyowati; Anna Aisyah Prihatin (STKIP Subang, 2024)
Application of Smart Citizen Spinner (SCS) Learning Media in the Last Hour of Pancasila History Material to Increase Students' Interest in Learning in Class VII H at SMP Negeri 12 Surabaya. This research aims to determine the increase in students' interest in learning through the Smart Citizen Spinner (SCS) learning media during the last lesson hour. Action Research (PTK) with a model design according to Kemmis and Mc which consists of planning, implementation, observation and reflection which was carried out in the first semester of the 2024-2025 academic year. The research subjects were 34 class VII H students. This research instrument uses observation sheets and questionnaires to collect quantitative data. Data analysis techniques use quantitative data. Based on the results of the questionnaire given to research subjects, it was found that cycle one data got a percentage of 38.23% and in cycle two it got a percentage of 94.11%. So it can be concluded from research that using the Smart Citizen Spinner (SCS) learning media can increase students' interest in learning in the History of Pancasila material at SMP Negeri 12 Surabaya.